Analysis of Road Maps ELT Textbook Series: A Semio-Cultural Conceptualization Perspective - Molavi, Somayeh; Debreli, Emre (Cross-Cultural Education Studies, 2025)
Language is not just a system of communication but a carrier of cultural meaning and values. Therefore, ELT textbooks as the main resources of teaching English should reflect sociocultural realities, promoting intercultural understanding and communicative competence. Accordingly, study aims to examine the semiotic relationship between text (as a sign) images (as an object) and students’ perception (as an interpretant) in the Road maps textbook A1 and B1 series taught at the preparatory school of Cyprus International University. Three pictures from beginner (A1) level and three pictures from intermediate (B1) level were chosen to analyze whether the relationship between textual and visual elements for students was denotational or connotational from a Semio-cultural conceptualization perspective. This perspective emphasizes the importance of analyzing language materials, such as textbooks, through a semiocultural lens to identify the cultural messages conveyed. The study draws on a new analytical framework as the tool for analyzing data that incorporates elements of semiotics into cultural conceptualization in the field of cultural linguistics. The study found that at the A1 level the relationship between sign, object and interpretant for students is connotational, that is, guided by the teacher (guided semiosis) and for B1 students, it is comprehended denotational. In addition, the results of the semi-structured interview with ten English teachers who are teaching the same books at the CIU show that individualism, westernization, globalization, family values, and traditional gender roles are Cultural conceptualizations and categories used in these textbook series.